Maintenance therapy after Autologous Stem Cell Transplantation in Multiple Myeloma – currents and perspectives (Journal of Medical Science, 2024)
MM is non-curable cancer that arises from plasma cells and is the second most common type of blood cancer. Drug-refractory relapses are inevitable, making it essential to sustain long-lasting remissions as part of therapy. Lenalidomide maintenance until progression is a standard of care for transplant-eligible newly-diagnosed patients. However, poor outcomes of high-risk patients and the risk of secondary primary malignancies associated with maintenance underline the need for novel approaches. Significant changes in frontline treatment maintenance are expected, with the increasing importance of minimal residual disease monitoring and the development of novel drug combinations for maintenance. This article explores current standards and prospects for maintaining response after upfront in ASCT in MM.